Scada for Prototype of Double Track Railroad Gate Arm Automation Based on PLC M221 - Setiyani, Theresia Prima Ari; Salim, Dede Kurniawan (SENATIK STT Adisutjipto, 2019)
Most of the gate arm at railroad crossings in Indonesia still using manual systems. Operator error and failure of a manual gate arm operate are factors in the occurrence of accidents on the railroad crossing. SCADA for railroad gate arm is an automation control system to open and close a railroad gate arm that has 2 lanes (double track). The system uses a PLC Schneider M221 as a controller and an HMI as an interface. The HMI allows operators to monitor system conditions in real-time. Four pairs of photosensors on the right and left side of the gate arm are used to detect trains in each lane. Information from the photosensor is processed by the PLC to control the gate arm motor, buzzer, indicator lights, and information display to the HMI. There are 2 operation modes, automatic and manual. In automatic mode, when the photosensor detects a train is about to pass, the gate arm closes, the buzzer goes on, the red light flashes. After the photosensor detects that the train has passed, the gate arm will open, the buzzer will off, and the green light will off.  if the photosensor are damaged then manual operation mode is using by pressing the open or close button.